Drinking in the Context of Life Stressors: A Multidimensional Coping Strategy Among South African Women. (1st January 2014) - Choi, Karmel W.; Watt, Melissa H.; MacFarlane, Jessica C.; Sikkema, Kathleen J.; Skinner, Donald; Pieterse, Desiree; Kalichman, Seth C.
Abstract : This study explored narratives of drinking as a coping strategy among female drinkers in a South African township. In 2010–2011, we conducted qualitative in-depth interviews with 54 women recruited from 12 alcohol-serving venues. Most women drank heavily and linked their drinking to stressors. They were motivated to use drinking to manage their emotions, facilitate social engagement, and achieve a sense of empowerment, even while recognizing the limitations of this strategy. This study helps to contextualize heavy drinking behavior among women in this setting. Multifaceted interventions that help female drinkers to more effectively manage stressors may aid in reducing hazardous drinking.